Self-efficacy and emotionally dysregulated behaviour: An exploratory test of the role of emotion regulatory and behaviour-specific beliefs - Hasking, Penelope; Boyes, Mark; Greves, S. (Elsevier Ireland Ltd, 2018)
We examined the relationship between self-efficacy and three behaviours that can serve similar affect-regulatory functions (self-injury, risky alcohol use, disordered eating). We proposed that general self-efficacy would be indirectly related to each outcome, operating via emotion regulatory self-efficacy and behaviour-specific self-efficacy. A path analysis confirmed this proposal in a sample of 490 university students, who completed questionnaires assessing the constructs of interest. Emotion regulatory self-efficacy was a salient predictor of self-injury and disordered eating, evidencing both direct and indirect relationships. Self-efficacy to resist each of the behaviours was uniquely related to its target behaviour. We discuss these findings, outlining the implications for a theoretical understanding of emotion-regulatory behaviours, and offer suggestions for prevention and early intervention initiatives.